Jawabanmu

2014-04-28T11:37:42+07:00
Sumbu x : A' (x,-y)
               A' (2,3)
sumbu y: A' (-x,y)
              A' (-2,-3)
x=3 : A' (2.a-x,y)
         A' (2.3-2,-3)
         A' (6-2,-3)
         A' (4,-3)
y=5 : A' (x,2.b-y)
         A'(2, 2.5-(-3))
         A'(2,10+3)
         A' (2,13)
y=x : A' (y,x)
         A' (-3,2)
y=-x : A' (-y,-x)
         A' (3, -2)
2014-04-28T12:47:18+07:00
Sumbu x = A' (2 , 3)
sumbu y = A' (-2 , -3)
x=3 = A' (2.3-2 , -3)
          (4,-3)
y=5 = A' (2 , 2.5--3)
          (2 , 13)
y=x   = A' (-3 , 2)
y=-x  = A'(3 , -2)
1 5 1